The Effectiveness of The Full-Day School System in Improving Academic Achievement and Character Development of Students: A Systematic Literature Review - Erka Pulungan; Ummi Rasyidah (Student Scientific Creativity Journal, 2026)
The Full Day School (FDS) system has been widely implemented across various levels of education in Indonesia as a strategy to holistically improve learning quality. However, studies that systematically integrate findings across educational levels remain limited. This study aims to synthesize empirical evidence on the effectiveness of FDS implementation in improving students' academic achievement and character building across educational levels through a Systematic Literature Review (SLR) approach guided by the PRISMA 2020 protocol. Literature searches were conducted on Google Scholar, SINTA, ERIC, and accredited national journal portals covering publications from 2020 to 2026. Of 124 articles initially identified, 31 met the inclusion criteria and were analyzed using a thematic approach with inter-rater reliability of 87%. Findings indicate that: (1) systematic, diagnostically-informed, and collaborative lesson planning constitutes the primary foundation of FDS success; (2) active learning methods including project-based learning, contextual teaching, STEAM integration, blended learning, and digital media significantly enhance student engagement and academic outcomes; and (3) well-managed FDS produces positive impacts on both cognitive achievement and character development (discipline, independence, religiosity, social skills) across elementary and secondary levels. Moderating variables including teacher quality, parental engagement, and time management are identified as key mediators. Gaps remain regarding senior high school-level quantitative studies, longitudinal designs, and comparative Islamic versus regular FDS research.